Relações contratuais em estruturas cooperadas : um estudo em sistemas agroindustriais suinícolas - Costa, Daniele de Lourdes Curto da (2012)
On this essay the aim was to discuss the role of contracts in the relations between cooperatives and their partners in specific transactions and where attributes of transaction and measurement are present. To do so, as the main theoretical basis we used the Transaction Costs Theory by Williamson (1985) and Measurement costs theory by Barzel (2005), beyond theories Contract and Agency. To attend this purpose, the goal of the present study was to understand how the attributes of transaction and measurement influence the contractual relations between producers and processors in swine cooperate structures, located in the west of Paraná. So, a qualitative research was developed, on a descriptive nature in two cooperatives in the west of Paraná. In relation to secondary data, these were obtained through Organização Brasileira de Cooperativas (Brazilian Cooperative Organization), Research Institutes, Agriculture Secretariat and related organs, both related do cooperatives and swine activity. In relation do primaty data, these were collected through semi-structured interview with producers and cooperatives. To attend the proposed methodology, the cooperatives should, necessarily, be involved with swine slaughter, processing or commercialization. As for producers, 20 cooperative ones were interviewed in loco, 10 from each cooperative. To choose these the criteria were: two producers with more than five years inside the cooperative and with contractual relations for at least three years; twelve producers with more than ten years inside the cooperative and with contractual relations for at least five years; six producers with more than fifteen years and more than ten under contract. With data analysis it was possible to observe that the governance structure is characterizes as hybrid, ever having the presence of high specificity of actives, but that is justified by the possibility of measuring. In relation to the formal contract, this one has relevance for the parts in the sense of bringing guarantee and continuity for the activity. On this case, the study has revealed that the formal contracts contribute for the producers to develop the activity, attending the expectations of the cooperative in obtaining a pattern and a greater control over the transacted active. However, concerted aspects involving specificity and measurement, can generate property rights loss for the producers. It was observed that they end up prevailing in non-hired margin relations, once the formal contract demands much flexibility and opening for future renegotiations, mainly related to infrastructure, management and measurement of the swine. It was also identified that the contracts start performing a double role in relation to the parts. First due to the specific investment of the parts, trying to avoid a possible opportunist behavior searching, this way, the balance in the transaction. Second, they are used, yet, as a mechanism to keep the cooperative swine producer as a faithful partner in the cooperative, acting as maintenance form in the agent and main relation.